High-performance self-doped V4+-V2O5 ion storage films grown in situ using a novel hydrothermal-assisted sol-gel composite method. (1st February 2022) - Liu, Hongying; Liang, Xiaoping; Jiang, Tao; Zhang, Yuanyang; Liu, Shiwei; Wang, Xuezhuang; Fan, Xiaowei; Huai, Xuguo; Fu, Yadong; Geng, Zhenbo; Zhang, Dequan
Highlights: V2 O5 ion storage nanofilm was prepared on ITO substrate by a novel sol-gel method. There was no seed layer and additives in situ hydrothermal-assisted sol-gel method. The annealing affects oxygen vacancy concentration, and in turn affects on ion storage capacity. The electrochromic device assembled with V2 O5 film showed excellent performance. Abstract: The advancement of efficient ion storage film is a formidable challenge. A kind of self-doped V 4+ -V2 O5 ion storage nanofilm on ITO-coating glass substrate is prepared in situ by a novel hydrothermal-assisted sol-gel composite method, which is without seed layers of hydrothermal process and additives of traditional sol-gel method. There are two important factors for the growth of V2 O5 nanofilm, that is, heterogeneous nucleation during hydrothermal method and the electrostatic attraction between V2 O5 sol and ITO substrate. A small amount of oxygen vacancies are introduced into V2 O5 lattice during the hydrothermal process, and the oxygen vacancy concentration is controlled by annealing treatment (200∼400 °C), which significantly improve the storage capacity and Li + diffusion. The excellent cycling performance of 300 °C-V2 O5 nanofilm is attributed to the synergistic effect of the gradient oxygen vacancies and the good bonding force between the film and the substrate. Comparing with the ion storage capacity of V2 O5 film prepared by traditional sol-gel method with the same annealing treatment (17.88 mC cm −2 ) and V2 O5 film without annealing treatment (17.79 mC cm −2 ), 300 °C-V2 O5 film has the highest ion storage performance, whose initial value of ion storage is up to 112.25 mC cm −2 and cycling stability is excellent with only a 2.4% decrease after 2000 cycles. The electrochromic device (ECD) with 300 °C-V2 O5 nanofilm as ion storage layer and WO3 as the electrochromic layer has been successfully assembled, which shows fascinating performance. Graphical abstract: Image, graphical abstract